JARINGAN AKTOR DALAM TATA KELOLA KOLABORASI PENGEMBANGAN EKONOMI KREATIF DI KABUPATEN SUBANG - Lentera Ilma; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The creative economy in Subang Regency has considerable potential and has been supported by policies, institutional arrangements, and the involvement of actors within the pentahelix model; however, its collaborative governance has not yet operated optimally. The problem addressed in this study lies in the lack of alignment in the vision, interests, and roles among actors, the still limited capacity of some creative economy actors, and the unclear coordination mechanism in creative economy development. This study aims to analyze the actors involved and the stages of the actor network in the collaborative governance of creative economy development in Subang Regency. This research employs a descriptive qualitative approach based on Actor-Network Theory (ANT) and the actor identification concept of Olander and Landin (2005). Data were collected through in-depth interviews, observation, and documentation with informants selected through purposive sampling and further developed using snowball sampling. The findings show that the Department of Tourism, Youth and Sports (Disparpora), the Creative Economy Committee (KOEKRAF), and Subang Creative Hub are the key actors in the collaborative network. The stages of punctualization and translation have been relatively well implemented; however, problematization, interessement, enrollment, and irreversibility have not been optimal due to uneven actor participation, limited dissemination of information, incomplete mapping of creative subsectors, and coordination still influenced by differences in vision. This study recommends clarifying role distribution, promoting more inclusive participation from the planning stage, and strengthening coordination and sustainable regulatory support.